The Upkeep of Human Rights and Social Justice: The Role of Right to Information Act 2009: A Study on Sylhet Division - Samiul, Mohammad Samiul Islam; Swati , Zayeda Sharmin PhD (Advances in Social Sciences Research Journal, 2020)
The study aim is to present how upkeep human rights and social justice in a society by the execution of RTI Act 2009. For this the study has focused on awareness of people about RTI, looking for government initiatives by which people learned about it, how eradicate corruption from the DC offices by the execution of RTI, and human rights and social justice endorsed by this law. This is a fundamental study in nature. Mixed approach has been followed. Both qualitative and quantitative data have been used in this study. Primary data collected by interview schedule with closed and open ended questions. Secondary data collected from the different published books, journal, articles and research report. The study findings are still inadequate for service providing and some of these are due to lack of information from officers and their support staffs, technological inefficiency as well as colonial legacy of civil servants etc. Mainly the study reveals that still the field administration has not become people oriented in respect of free flow of information so far. But both discussion of theoretical as well as field study proved that RTI law implementation and defending human rights and social justice have strong relationship at the local level. So the outcome of this study has proven that proper execution of RTI law can protects human rights and justice in the society.